Standar Kritik Sastra Arab pada Masa Kontemporer (Perspektif Ahmad Asy-Syāyib dalam Buku Uṣūl Al-Naqd Al-Adabiy) - Nur'aini, Siti; Arsyad, Hafid; Tasnimah, Tatik Maryatut (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
Contemporary Arab literary criticism has established certain standards of evaluation, significantly differing from the periods of Jahiliyyah to the Umayyad era. This research aims to elucidate the standards of Arab literary criticism in contemporary times, focusing on the book "Uṣūl al-Naqd al-Adabiy" by Ahmad Asy-Syāyib, one of the contemporary literary figures and critics. The research methodology employed a descriptive qualitative approach, specifically a literature review. The findings reveal that contemporary Arab literary criticism encompasses objective aspects related to language, style, and literary structure, as well as subjective aspects dependent on individual preferences. Additionally, Ahmad Asy-Syāyib emphasizes the importance of preserving and valuing the uniqueness of Arab literature in the realm of literary criticism amidst modernization trends and Western influences.Keywords - Ahmad Asy-Syāyib, Arab Literary Criticism, Contemporary, Uṣūl Al-Naqd Al-Adabiy.